RANCANGAN FASILITAS KERJA PADA STASIUN PENGAYAMAN KERANJANG BERDASARKAN ANALISIS POSTUR KERJA DENGAN METODE RULA (RAPID UPPER LIMB ASSESMENT) PADA UD. MAULANA BERASTAGI - Darnianti Darnianti; AJIS SAMPURNO (Universitas Quality, 2019)
Problems arising in basket sacrificial stations that workers often complain or feel a complaint. This may occur in the long term which may cause injury to the worker. Rappid Upper Limb Assessment (RULA) is a method used to assess posture on the worker, covering the back, shoulders, neck, upper hand, and wrist. This method includes a quick identification of work attitudes that potentially lead to occupational accidents of concern of this method is the musculoskeletal system. The purpose of this research is to analyze the work posture on the workers in the weaving station. In the worker known that 12.41% said not sick, 37.25% said somewhat ill, 40.52% said ill, and stated very ill 9.8%. Another goal of the study was to identify postures that have Musculoskeletal injury risks. Based on the results of data processing, it is known that all work postures have a risk of injury.